1994
DOI: 10.1111/j.1472-765x.1994.tb00947.x
|View full text |Cite
|
Sign up to set email alerts
|

A β-N-acetylhexosaminidase from Penicillium oxalicum implicated in its cell-wall degradation

Abstract: High β‐N‐acetylhexosaminidase (EC.3.2.1.52) activity was detected during autolysis of Penicillium oxalicum. Purification of the enzyme to homogeneity yielded an enzyme with a molecular weight of 132 000 Da by gel filtration and 71 900 Da by SDS polyacrylamide gel electrophoresis, suggesting a dimeric structure. The enzyme is an acidic protein with a pl of 5.0. Optimal activity was at pH 4.0 and 40°C, with a Km of 0.80 mmol 1‐1 for p‐nitrophenyl‐β‐N‐acetylglucosaminide and 1.03 mmol 1‐1 for p‐nitrophenyl‐β‐N‐ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Similar to other analogous age-related fungal enzymes (REYES and BYRDE 1973, YAMA-MOTO et al 1985, 1986, REYES et al 1989, RODRÍGUEZ et al 1994, VAN TILBURG and THOMAS 1994), the purified P. chrysogenum HexNAc©ase split PNP-GlcNAc, PNP-GalNAc and N,N'-diacetylchitobiose but in this case no liberation of GlcNAc was detected in the presence of N,N',N''-triacetylchitotriose (Table 2). That is P. chrysogenum HexNAc©ase possessed much narrower substrate specificity for chitin oligomers than other age-related fungal HexNAc'ases and GlcNAc'ases (YAMAMOTO et al 1985, 1986, REYES et al 1989, RODRÍGUEZ et al 1994.…”
Section: Substrate Specificity Investigationssupporting
confidence: 73%
See 2 more Smart Citations
“…Similar to other analogous age-related fungal enzymes (REYES and BYRDE 1973, YAMA-MOTO et al 1985, 1986, REYES et al 1989, RODRÍGUEZ et al 1994, VAN TILBURG and THOMAS 1994), the purified P. chrysogenum HexNAc©ase split PNP-GlcNAc, PNP-GalNAc and N,N'-diacetylchitobiose but in this case no liberation of GlcNAc was detected in the presence of N,N',N''-triacetylchitotriose (Table 2). That is P. chrysogenum HexNAc©ase possessed much narrower substrate specificity for chitin oligomers than other age-related fungal HexNAc'ases and GlcNAc'ases (YAMAMOTO et al 1985, 1986, REYES et al 1989, RODRÍGUEZ et al 1994.…”
Section: Substrate Specificity Investigationssupporting
confidence: 73%
“…That is P. chrysogenum HexNAc©ase possessed much narrower substrate specificity for chitin oligomers than other age-related fungal HexNAc'ases and GlcNAc'ases (YAMAMOTO et al 1985, 1986, REYES et al 1989, RODRÍGUEZ et al 1994. Interestingly, a HexNAc©ase with very similar substrate specificity to that of the P. chrysogenum GlcNAc'ase was isolated from growing hyphae of Mucor rouxii (LINDER 1987, RAST et al 1991, MAYER et al 1993).…”
Section: Substrate Specificity Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result can be explained by the second substrate being a polymer, so that its complete degradation could need the action of different enzymes. In fact, this group have reported the synergistic action of this enzyme with a /3-N-acetylhexosarninidase when a chitin fraction of P. oxalicum cell wall was used as substrate (Rodriguez et al 1994). The viscosimetric study showed the highest affinity of the enzyme for carboxymethyl chitin (33.0 U ml-').…”
Section: Molecular Weight Standardsmentioning
confidence: 99%
“…The activity belongs to a lytic complex produced by this fungus, implicated in its cell wall degradation (Copa-Patiiio et al 1990a). A B-glucanase, Bglucosidase and f3-N-acetylhexosaminidase have already been purified and characterized in our laboratory (Copa-Patiiio et al 1989, 1990bRodriguez et al 1994) from this lytic complex.…”
Section: Introductionmentioning
confidence: 99%